TVET Leadership in the Education 4.0: Characteristics, Opportunities and Challenges - Fiandra, Y A; Jalinus, N; Refdinal, Refdinal; Anwar, M; Waskito, Waskito (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2021)
There are many factors that determine the success of vocational or vocational education, this research focuses on leadership factors in vocational education in the 4.0 education era. This research then examines matters relating to what are digital opportunities related to the presence of the 4.0 education era and analyzes the challenges that may be an obstacle to picking up opportunities or conveniences in the current digital era. The method used in this study is library research using three main stages in analyzing articles, starting from the stage of collecting, integrating and finally identifying the summary of the articles being analyzed. The results of this study reveal that transformational leadership, digital tools in the form of interactive multimedia and obstacles that often hinder education 4.0 such as internet access are the main points that often arise in answering research questions.